FAKTOR YANG MEMPENGARUHI NILAI EKSPOR MINYAK SAWIT INDONESIA KE BEBERAPA NEGARA ASIA - Putra, Golda Heda; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 11 (2022): vol.11.11. NOVEMBER 2022[4011-4233], 2022)
The purpose this study to analyze effect of GDP, foreign exchange rates, and population simultaneously and partially on value palm oil exports to India, China, Pakistan, Bangladesh, and Singapore. The research locations in this study in several countries Asia, including India, China, Pakistan, Bangladesh, and Singapore from 2015 to 2020. The data used secondary data, analyzed by multiple linear regression analysis. The results of the study show that GDP, exchange rates, and population simultaneously influence the value of Indonesian palm oil exports to several Asian countries. GDP partially has a negative and significant effect on the export value of palm oil, the exchange rate partially has a positive and significant effect on the export value of palm oil, and the population partially has a positive and insignificant effect on the export value of Indonesian palm oil to several Asian countries. Keywords: GDP, exchange rate, population, exports, palm oil